2020
DOI: 10.3390/cancers12010127
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Label-Free Isolation of Heterogeneous Circulating Tumor Cells and CTC Clusters from Non-Small-Cell Lung Cancer Patients

Abstract: (1) Background: Circulating tumor cell (CTC) clusters are emerging as clinically significant harbingers of metastases in solid organ cancers. Prior to engaging these CTC clusters in animal models of metastases, it is imperative for technology to identify them with high sensitivity. These clusters often present heterogeneous surface markers and current methods for isolation of clusters may fall short. (2) Methods: We applied an inertial microfluidic Labyrinth device for high-throughput, biomarker-independent, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…Vimentin positive CTCs in advanced NSCLC patients are of high abundance indicating the involvement of EMT in drug resistance 30 , 46 . According to a very recent study, based on a similar size-based CTC enrichment methodology, the majority of recovered CTCs/clusters were EpCAM-negative, suggesting that these cells would have been missed using traditional antibody-based capture methods 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin positive CTCs in advanced NSCLC patients are of high abundance indicating the involvement of EMT in drug resistance 30 , 46 . According to a very recent study, based on a similar size-based CTC enrichment methodology, the majority of recovered CTCs/clusters were EpCAM-negative, suggesting that these cells would have been missed using traditional antibody-based capture methods 47 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of CTCs isolated from breast cancer patients and mouse models, reported that the binding sites for CSC transcription factors such as OCT4, SOX2, or NANOG, are hypomethylated in CTC clusters compared with isolated CTCs [49]. Other data collected from human samples also emphasize the presence of hybrid E/M phenotypes in heterogeneous CTC clusters, particularly in lung cancers [51,52,109,190]. Very elegantly, a study by Yu and coworkers identified cells expressing both epithelial (such as EpCAM or cytokeratins) and mesenchymal markers (including fibronectin, N-cadherin or PAI-1) in isolated CTCs but also in CTC clusters from breast cancer patients [179].…”
Section: Traveling In Clustersmentioning
confidence: 98%
“…Several filter-based assays exploit the knowledge that most hematopoietic cells are smaller (<10 µm) than CTCs (>10 µm) [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. A profusion of recently conceived microfluidic devices also uses the size and/or the deformability parameters [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Finally, CTC isolation devices, many also being microfluidic-based [ 59 , 60 , 61 , 62 , 63 ], use dielectrophoresis (DEP) to differentiate tumor cells from normal cells by their electric charges [ 64 ].…”
Section: Ctc Enrichment Identification and Isolation Techniquesmentioning
confidence: 99%
“…CTCs are found either as single cells or in clusters, while their phenotypic analysis has shown significant intra- and inter-patient heterogeneity [ 4 ]. The detection of CTCs in clusters and their contribution in metastasis and poor outcome of patients has been highlighted in various cancers [ 5 , 6 , 7 , 8 ]. The molecular characteristics and properties of clusters are different from those of single CTCs [ 6 , 7 ] and their size considerably varies, from 2 to 100 CTCs [ 4 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%